Enhancing Arabic Language Learning in Class VIII MTsN 5 Jombang: An Evaluation Using the CIPP Model - Muslimah, Maziyyatul; Alfatihah, Aini; Fitriah, Nur Izzati; Maftuhah, Siti (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2024)
This qualitative study used CIPP model to assess Arabic language learning for Class VIII at MTsN 5 Jombang. Data collection was carried out by interviews, observation and documentation. The research respondents consisted of 3 Arabic teachers and 29 students of Class VIII-F, including 15 boys and 14 girls. Analysis of the findings including contextual, input, process and product dimensions. The results show that Arabic learning is enhanced by a supportive environment, good infrastructure, and cultural elements with rich Islamic cultural heritage. The program is supported by a balanced curriculum and well-equipped facilities. However, the curriculum must be updated following the latest national curriculum, Emancipated Curriculum, and teachers must be trained to remain relevant. Constant supervision is required to improve the quality of teaching and student engagement. The results of the evaluation showed that 80% of students met the minimum competency standards. However, more interactive teaching for speaking skills need improvement.